Reviews of environmental contamination and toxicology volume 217 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2012)
CONTENTS Foreword Preface Chiral Pesticides: Identification, Description, and Environmental Implications Elin M. Ulrich, Candice N. Morrison, Michael R. Goldsmith, and William T. Foreman Strategies for Chromium Bioremediation of Tannery Effluent Satyendra Kumar Garg, Manikant Tripathia and Thiruneelakantan Srinath Index